1973
DOI: 10.1007/bf02253311
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale precipitation estimates using satellite data; Application to the Indian Monsoon

Abstract: Thirty months of continuous low resolution statellite measurements of albedo and emitted longwave radiation are used to study precipitation associated with the Indian Monsoon. Combined with rainfall data for the Indian subcontinent, the satellite data are employed to develop a precipitation intensity index. It is postulated that such an index must first adequately depict the extreme monsoon rainfall regime before it can be applied to the study of rainfall over other regions, especially those devoid of conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Satellite data offer much better resolution, but Until the launch of Cosmos 243 in 1968 and Nimbus 5 in 1972, all satellite data were from the visible or infrared portions of the electromagnetic spectrum in which precipitation cannot be observed directly because of the opacity of clouds. (See Martin and Scherer [1973] and Dittberner and Vonder Haar [1973] for a review of precipitation estimation techniques using visible and infrared satellite data.) Several authors have shown the usefulness of microwave imagery from the Nimbus 5 electrically scanning microwave radiometer (ESMR) in depicting oceanic precipitation zones [Theon, 1973;Sabatini and Merritt, 1973;Allison et al, 1974a, b;Wilheit et al, 1976].…”
Section: Introductionmentioning
confidence: 99%
“…Satellite data offer much better resolution, but Until the launch of Cosmos 243 in 1968 and Nimbus 5 in 1972, all satellite data were from the visible or infrared portions of the electromagnetic spectrum in which precipitation cannot be observed directly because of the opacity of clouds. (See Martin and Scherer [1973] and Dittberner and Vonder Haar [1973] for a review of precipitation estimation techniques using visible and infrared satellite data.) Several authors have shown the usefulness of microwave imagery from the Nimbus 5 electrically scanning microwave radiometer (ESMR) in depicting oceanic precipitation zones [Theon, 1973;Sabatini and Merritt, 1973;Allison et al, 1974a, b;Wilheit et al, 1976].…”
Section: Introductionmentioning
confidence: 99%
“…Another algorithm includes the bispectral approach, which are discussed in the studies conducted by Tsonis and Isaac (1985), Lovejoy and Austin (1979a,b), and Dittberner and Vonder Haar (1973). In this technique, cold/bright and warm/dark cloud radiances are cross‐analyzed in order to determine the probability of precipitation.…”
Section: Remote Sensing Techniquesmentioning
confidence: 99%